Global burden of disease changes related to high red meat diets and breast cancer from 1990 to 2021 and its prediction up to 2030 - Tong, Yujun; Ning, Hong; Zhang, Zhen; Zhang, Xiaohong; Tu, HongMei; Yang, Min; Li, Xiaoan; Liang, Tiantian (Frontiers in Nutrition, 2025)
BackgroundBreast cancer associated with high red meat consumption has become a significant global health issue. This study aims to analyze the global and regional disease burden related to breast cancer attributable to high red meat diets from 1990 to 2021, and to predict future trends in disease burden through 2030, providing scientific evidence for the development of targeted public health strategies.MethodsData were extracted from the Global Burden of Disease (GBD) database, focusing on breast cancer-related attribution indicators, including the age-standardized rates (ASRs) of mortality, years of life lost (YLLs), years lived with disability (YLDs). The study analyzed the changes in breast cancer disease burden associated with high red meat consumption from 1990 to 2021 at the global level, across 21 regions, and in 204 countries. Future trends were projected using the Bayesian Age-Period-Cohort (BAPC) model.ResultsIn 2021, breast cancer deaths attributable to excessive red meat diets totaled 81,506, with YLLs amounting to 2,135,620 person-years and YLDs accounting for 214,442 person-years. These values represent increases of 80.83, 72.69, and 65.37%, respectively, compared to 1990. Despite global decreases in the ASRs of mortality and YLLs (which decreased to 1.15/100,000 and 30.12/100,000, with EAPCs of −0.77 and −0.73, respectively), the ASR of YLDs remained relatively stable (EAPC of −0.12). Stratification by Socio-Demographic Index (SDI) revealed a significant decline in disease burden in high-SDI regions, while the ASR in low-SDI regions trended upward. Projections suggested that by 2030, the global ASR of breast cancer burden may stabilize, while the burden in low-SDI regions is expected to continue rising.ConclusionFrom 1990 to 2021, the global age-standardized rate of the breast cancer disease burden decreased, but disparities between regions with different SDI levels remain a major challenge. In the future, it is essential to prioritize addressing the burden in low-SDI regions and developing targeted interventions to optimize health resources, thereby mitigating the public health threat of breast cancer.